1036 Improving estimates of the costs of injury in Western Austarlia using linked data. (1st September 2016) - Hendrie, Delia; Miller, Ted; Randall, Sean; Brameld, Kate
Abstract : Background: Previous estimates of the costs of injury in Australia have relied heavily on secondary data, including from international sources. The availability of linked health data and other relevant datasets such as police reports of road crashes and personal injury motor vehicle insurance claims data has provided the opportunity to produce Australian-based estimates of the cost of injury using improved methods. Methods: A retrospective, population-based design was adopted in the study. Health data including emergency department presentations, hospital admissions and death data were linked with police crash report records and motor vehicle personal injury claims data by the Data Linkage Branch at the West Australian Health Department for 2002 through to 2014. Episodes of injury were determined using the linked health data, with clear zones established to account for return visits for the same injury. Corresponding injury costs were estimated based on generalised linear modelling of component costs of the injury claims data, with quality of life loss calculated from Global Burden of Disease disability weights. Results: Problems encountered in regards to the identification of episodes of injury will be discussed, in particular in regard to establishing clear zones. Similarly, issue in modelling from injury claims data for road injury casualties to all injury case will be highlighted. Previous estimates of the costs of injury will be compared with estimates based on the linked data approach and difference explored. Trends in injury costs in Western Australia over the past 10-years will be analysed by socio-demographic and injury characteristics. Conclusions: Injuries are known to impose a significant health and social burden on individuals, families and the community. Applying improved methods of estimating these costs will provide the basis for better policy, planning and targeting of injury prevention strategies.